ESI in English - Polastri, Vanesa; Saubidet Oyhamburu, Stella Maris (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
Are you a teacher, a linguist and/or a researcher in the field? Have you ever thought of the importance of decolonising the syllabus? Do you enjoy being part of a community of practice? Can a Freirian perspective enrich the English class? Do renowned speakers exert any influence on regular classes at school? Is CSE part of our lessons? Some answers and new questions can be found in this project called ESI in English. ESI in English is a multiplatform project envisioned and carried out by Paola Cossu and Gabriela Brun, EFL teachers, teacher educators and Comprehensive Sexuality Education (CSE) advocates from Junín, province of Buenos Aires. They created the esi.in.english Instagram and Facebook accounts in the second half of 2019 when they started delivering workshops at different higher education institutions and lectures at national congresses. The purpose sought with the opening of these virtual spaces was to promote dealing with social justice and CSE issues in the English language classroom in all the levels of the educational system. These accounts work as a repository of teaching resources and, above all, as a dynamic exploration of diverse voices that enter into dialogue to contribute to continuing professional development of English as a Foreign Language (EFL) teachers and to enable the questioning of traditional practices that perpetuate uneven power relations and inequity both in the classroom and outside its walls. They invite, as Freire did, teachers-students and students-teachers to transform reality: “To surmount the situation of oppression, people must first critically recognize its causes, so that through transforming action they can create a new situation, one which makes possible the pursuit of a fuller humanity” (2005 [1970]: 47). bel hooks (2006 [1994]) holds that it is by choosing love that “we are best positioned to transform society in ways that enhance the collective good”. These complementary views on education for freedom through love have given roots and inspiration to these channels of communication from, to and with the teaching community.